Evaluating English Teacher Education Programs in Indonesian Tertiary Education: A Proposed Model - Didin Nuruddin Hidayat (IJECA (International Journal of Education and Curriculum Application), 2018)
Numerous research studies on language program evaluation in many countries, for instance, Turkey (Uysal, 2012), Taiwan (Chang, 2010), Bangladesh (Rahman, 2007), Saudi Arabia (Liton, 2013) have yielded valuable ideas and insights in improving the quality of language programs. Those research studies have also expanded the plethora of discussion and have tested many ‘untested’ thoughts in the area of language program evaluation. Nonetheless, similar studies have not been researched much far in the Indonesian education context. The present study aims to describe the importance of English teacher education program evaluation. Also, the study aims to explore a suitable evaluation model in evaluating English teacher education programs, particularly in the Indonesian tertiary education context. The findings of the study found Peacock's (2009) model as a potential evaluation model to apply in evaluating English teacher education programs. These are based on at least three following grounds: suitable to the needs and environment of English teacher education in Indonesia, reliable and informative evaluation, and thorough involvement of the inner circle stakeholders. The study concludes that if an evaluation is conducted properly, then it has the potential to improve the quality of English language teachers training programs.